A Dashboard for System Trustworthiness Properties Evaluation - Camargo, Diego; Gaia, Felipe Nunes; Basso, Tania; Moraes, Regina Lúcia de Oliveira (Anais do Workshop de Testes e Tolerância a Falhas (WTF); 2020: Anais do XXI Workshop de Testes e Tolerância a FalhasDO - 10.5753/wtf.2020.12487, 2020)
Understanding the trustworthiness of a cloud system is a difficult task, because it encompasses a large diversity of properties such as security, privacy, performance, among others. Evaluating and improving the system regarding trustworthiness require the analysis of huge data considering their historical status. The goal of this paper is to present a dashboard developed for the visualization of these properties, the relationship among them and their relevance in the composition of a trustworthiness score over usage time.